THE CORRELATION ISSUES BETWEEN BIOGRAPHICAL AND OUTLIVING MEMORY (ON THE EXAMPLE OF HENRIK EDOYAN’S POETRY) - ZAKARYAN, HRIPSIME (Bulletin of Yerevan University E: Philosophy, Psychology, 2019)
This article is an attempt to analyze reflected in the poetry of the individual Henrik Edoyan’s and the unconscious archetypes of the collective unconscious. The inherent peculiarities of Henrik Edoyan’s poetic “I” and the poetic world are linked to the problem of the individual’s self-recognition and self-determination, one of the main components of it being the problem of proportionating the biographic and outliving memories.